A Review of the Goals of Learning Arabic among Indonesian Students at Domestic and Foreign Universities - Ahmad Fadhel Syakir Hidayat; Irwansyah, Irwansyah; Badrun Nisyam; Dimas Aditia; Muhammad Syihab As’ad; Adamu Abubakar Muhammad; Akhirudin, Akhirudin (Al-Jawhar : Journal of Arabic Language, 2024)
The increasing interest of Indonesian students in studying Arabic, both domestically and abroad, highlights the importance of this language in the context of globalization and intercultural interconnectivity. This interest is reflected in their various learning goals, ranging from understanding the Islamic religion to exploring the rich Arab culture. However, differences in learning contexts between studying at home and abroad may affect students' formulation of learning goals, motivation, and learning outcomes. This study aims to review the Arabic learning goals of Indonesian students at domestic and overseas universities. Using a descriptive quantitative approach, this study analyzes data from university students to understand their goals, confidence levels, and evaluations of Arabic language learning. The results show that most students have a high level of confidence in learning Arabic, with varied goals, with domestic students tending to be more about deepening religious knowledge and supporting their careers, while overseas students are more about deepening religious knowledge and communication skills. Different evaluation methods and perceptions of the learning environment reflect the differences in learning goals between domestic and international students. Overseas students tend to feel more supported and have greater access to support resources, while domestic students may face challenges obtaining adequate support. Despite this, both groups showed high confidence in achieving their learning goals.